2013
DOI: 10.1097/sga.0b013e3182945881
|View full text |Cite
|
Sign up to set email alerts
|

Further Validation of the Visual Analogue Scale for Irritable Bowel Syndrome After Use in Clinical Practice

Abstract: The Visual Analogue Scale for Irritable Bowel Syndrome (VAS-IBS), a self-rating questionnaire, was designed to measure symptoms and the effect of treatment in patients suffering from irritable bowel syndrome. The aim of this descriptive correlational study was to conduct further psychometric validation after the VAS-IBS had been used in clinical practice, translate it into English, and compare the results with controls. Forty-nine patients with irritable bowel syndrome (median age = 38 years old [range, 18-69 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…It is a validated questionnaire for estimation of the most common GI complaints that patients with non-organic, functional bowel disease experienced during the previous 2 weeks [33]. This scale has also been validated for estimation of symptoms over time [34]. The seven items measured in the VAS-IBS address the symptoms of abdominal pain, diarrhea, constipation, bloating and flatulence, nausea and vomiting, psychological well-being, and intestinal symptoms´ influence on daily life.…”
Section: Methodsmentioning
confidence: 99%
“…It is a validated questionnaire for estimation of the most common GI complaints that patients with non-organic, functional bowel disease experienced during the previous 2 weeks [33]. This scale has also been validated for estimation of symptoms over time [34]. The seven items measured in the VAS-IBS address the symptoms of abdominal pain, diarrhea, constipation, bloating and flatulence, nausea and vomiting, psychological well-being, and intestinal symptoms´ influence on daily life.…”
Section: Methodsmentioning
confidence: 99%
“…The Romanian VAS-IBS was translated from the ROME III version of the English VAS-IBS questionnaire (8). The permission for Romanian translation was obtained from Prof. Dr. Mariette Bengtsson from Malmo University.…”
Section: Translation and Adaptation To Romanian Language Thesaurus Amentioning
confidence: 99%
“…Because of the multifaceted character of IBS and the lack of molecular biomarkers to diagnose and observe the treatment efficiency, Bengtsson et al (6,7,8) considered that VAS-IBS could easily translate the patient perception on symptoms severity and wellbeing in numbers. However, even if Bengtsson et al (8) suggested that the English version of the VAS-IBS should be used in English-speaking countries and be further tested for validity and reliability with Englishspeaking patients, Romanian population is not a predominantly English-speaking population. Thus, in this study, we aimed to propose and validate the Romanian translation and adaptation of VAS-IBS scale.…”
Section: Introductionmentioning
confidence: 99%
“…VAS-IBS is a validated self-rating questionnaire for estimation of the most common gastrointestinal complaints in patients with nonorganic, functional bowel disease experienced during the last 2 weeks [19]. This questionnaire has also been validated for estimation of symptoms over time [20]. The seven items measured in the VAS-IBS address the symptoms abdominal pain, diarrhea, constipation, bloating and flatulence, nausea and vomiting, psychological well-being, and intestinal symptoms´ influence on daily life.…”
Section: Visual Analog Scale For Irritable Bowel Syndromementioning
confidence: 99%